Kegiatan Pengabdian Masyarakat Dalam Rangka Penapisan Kadar Protein Dan Profil Lipid Terhadap Sarkopenia Pada Kelompok Lanjut Usia - Frisca Frisca; Alexander Halim Santoso; Farell Christian Gunaidi; Edwin Destra; Vincent Aditya Budi Hartono; Kanaya Fide Kusuma; Alicia Herdiman (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The risk of sarcopenia and metabolic complications in the elderly can be caused by the aging process and decreased muscle mass in the elderly group. Sarcopenia and obesity in the elderly also increase the risk of cardiovascular disease, diabetes, and physical disability, which have the potential to reduce quality of life and increase morbidity and mortality. The purpose of this community service activity is to screen protein levels and lipid profiles in the elderly group in order to detect the risk of sarcopenia and dyslipidemia early. This activity is carried out using the Plan-Do-Check-Action (PDCA) method which includes planning, implementation, supervision, and follow-up. The community service activity was carried out at Panti Bina Bhakti, South Tangerang, involving 93 elderly participants aged >65 years. The results of the activity showed that 35 people (37.63%), 9 people (9.68%), 35 people (37.63%), and 7 people (7.53%) each had abnormal lipid profiles for HDL, Cholesterol, LDL, and Triglycerides. While 24 people (25.81%) had abnormal albumin levels. Therefore, it is necessary to monitor protein levels and lipid profiles regularly as well as early intervention through a healthy diet, regular exercise, and education for the elderly to maintain muscle mass and muscle strength.